Soybean response to molybdenum in sandy soils of low fertility - Tanaka, Roberto Tetsuo; Mascarenhas, Hipólito Assunção Antonio; Bulisani, Eduardo Antonio; Campidelli, Claudio; Dias, Otavio Souza (Pesquisa Agropecuaria Brasileira, 1993)
Most sandy soils present low reserves of plant nutrients. This is the main factor of low yields. Experiments were conducted during a period of three years in a Red-Yellow Latosol sandy phase originally under "cerrado vegetation", to verify the effect of Mo, chicken manure, micronutrients (Zn, B and Cu), and split application of K. There was an increase in soybean yields with application of Mo independently of its association with other treatments. Inspite of increasing the yield Mo did not alter the nutrient concentration of the leaves including that of N.